Makna Keberagamaan Mahasiswa Penerima Beasiswa STAIN Kudus - Efa Ida Amaliyah (Badan Litbang dan Diklat Kementerian Agama RI, 2020)
AbstractThis study reveals two things, firstly the significance of religiosity and the secondly, the form of religiosity according to Bidikmisi STAIN Kudus students. This research was conducted on STAIN Kudus students who received Bidikmisi scholarships, using a sociology approach. Bidikmisi students are students who have specialties in two fields, namely academic potential and Spiritual potential. In Academic potential, they have to compete with thousands of students, be preferred from the middle to lower classes. This is supported by good and satisfying academic abilities through tests conducted by the Ministry of Religion through STAIN Kudus. Spiritual potential, bidikmisi students get the opportunity to